2006
DOI: 10.20537/nd0601002
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of motion of A+1 vortices in a two-layer rotating fluid

Abstract: Получено 7 февраля 2006 г.Исследуются характерные свойства движений A + 1 погруженных в двухслойную жидкость точечных вихрей с A плоскостями симметрии. Предполагается, что центральный вихрь принадлежит верхнему слою, а равносторонняя A-гональная конфигурация вихрей равной интенсивности -нижнему. Приводится анализ теоретически возможных стационарных движений при A 2. Для A = 2 методами качественного анализа осуществлена классификация про-извольных движений вихревых структур, а также получены предварительные рез… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The other two elliptic points correspond to nontrivial collinear states representing a uniformly moving vortex triplet. Such a structure was called a triton in [188], [189], [190], [191]. The existence condition for a triton is specified by the dispersion equation 20) and the velocity of its motion by the equality…”
Section: Nonzero Total Momentummentioning
confidence: 99%
“…The other two elliptic points correspond to nontrivial collinear states representing a uniformly moving vortex triplet. Such a structure was called a triton in [188], [189], [190], [191]. The existence condition for a triton is specified by the dispersion equation 20) and the velocity of its motion by the equality…”
Section: Nonzero Total Momentummentioning
confidence: 99%
“…Note that, among carousel pentapoles, there is a static one for which l ¼ l ðPÞ S % 1:221; the pentapoles with l > l ðPÞ S rotate counterclockwise, and those with l < l ðPÞ S , clockwise. 24 So we can state that, in the carousel case, all counterclockwise pentapoles and the clockwise ones at l 0 < l < l ðPÞ S are unstable, whereas clockwise pentapoles with l < l 0 are stable to symmetric perturbations.…”
Section: Instability Of the Pentapolementioning
confidence: 93%
“…Ensembles of the first kind will be termed flat. Symmetric constantly rotating ensembles of the second kind were named carousels 24 or roundabouts 25 (in a later, concise English version of the same article); we will use the term "carousel. "…”
Section: B Ensembles Of Point Vorticesmentioning
confidence: 99%
See 1 more Smart Citation
“…0 ¼ s 0 ¼ 0) of the stationary problem was considered in the study by Sokolovskiy and Verron (2006); they showed that for any A, there exists a critical value cr 50, such that an appropriate solution exists whatever cr . The steady motion of the multipolar structure is a cyclonic rotation for 5 0 (a motion called inverse roundabout for which intralayer interaction is dominant); for ¼ 0 , steady states are found.…”
Section: Mathematical and Physical Frameworkmentioning
confidence: 99%